Evaluation of oil production from oil palm empty fruit bunch by oleaginous micro-organisms - Ahmad, Farah; Zhang, Zhanying; Doherty, William O. S.; O'Hara, Ian M. (Wiley, 2016)
Oil palm empty fruit bunch (EFB) is a readily available, lignocellulosic biomass that has potential to be utilized as a carbon substrate for microbial oil production. In order to evaluate the production of microbial oil from EFB, a technical study was performed through the cultivation of oleaginous micro-organisms (Rhodotorula mucilaginosa, Aspergillus oryzae, and Mucor plumbeus) on EFB hydrolyzates. EFB hydrolyzates were prepared through dilute acid pre-treatment of the biomass, where the liquid fraction of pre-treatment was detoxified and used as an EFB liquid hydrolyzate (EFBLH). The solid residue was enzymatically hydrolyzed prior to be used as an EFB enzymatic hydrolyzate (EFBEH). The highest oil concentrations were obtained from M. plumbeus (1.9 g/L of oil on EFBLH and 4.7 g/L of oil on EFBEH). In order to evaluate the feasibility of large-scale microbial oil production, a technoeconomic study was performed based on the oil yields of M. plumbeus per hectare of plantation, followed by the estimation of the feedstock cost for oil production. Other oil palm biomasses (frond and trunk) were also included in this study, as it could potentially improve the economics of large-scale microbial oil production. Microbial oil from oil palm biomasses was estimated to potentially increase oil production in the palm oil industry up to 25%, at a cheaper feedstock cost. The outcome of this study demonstrates the potential integration of microbial oil production from oil palm biomasses with existing palm oil industry (biodiesel, food and oleochemicals production), that could potentially enhance sustainability and profitability of microbial oil production.